Ammonium metavanadate: an effective catalyst for synthesis of alpha-hydroxyphosphonates - Sonar, Swapnil S.; Kategaonkar, Amol H.; Ware, Madhav N.; Gill, Charansingh H.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Arkivoc, 2009)
Ammonium metavanadate (NH(4)VO(3)) is an inexpensive, efficient and mild catalyst for the synthesis of alpha-hydroxyphosphonate derivatives by the reaction of various aryl or heteroaryl aldehydes with triethylphosphite at room temperature. This method affords the alpha-hydroxyphosphonates in short reaction times, under solvent-free conditions, and in high yield.
Keywords: Aldehyde; alpha-hydroxyphosphonate; Ammonium metavanadate (NH(4)VO(3)); Solvent-free; Triethyl phosphite

Green and sustainable approach to BIS-(INDOLYL) alkanes - Gholap, Somnath S.; Wakchaure, Prasad B.; Pandhare, Gajanan R.; Gill, Charansingh H. (Indian Journal of Heterocyclic Chemistry, 2009)
An efficient, high yielding, green and mild method has been developed for the synthesis of bis (indolyl) methanes using dodecylsulphonic acid as an effective surfactant type Bronsted acid catalyst in aq media. The method is excellent for various new bis-(indolyl) methanes derived from pyrazolaldehydes.

Ultrasound assisted one pot synthesis of imidazole derivatives using diethyl bromophosphate as an oxidant - Nagargoje, Deepak; Mandhane, Priyanka; Shingote, Savita; Badadhe, Pravin; Gill, Charansingh H. (Ultrasonics Sonochemistry, 2012)
A one pot, three-component condensation of benzoin/benzyl, an aldehyde, and ammonium acetate using diethyl bromophosphate as a mild oxidant is achieved to form trisubstituted imidazole compounds. Under ultrasound irradiation, a smooth condensation occurs to get the 2, 4, 5-triaryl-1H-imidazole compounds in good to excellent yields. The study explores the scope and limitation of diethyl bromophosphate as an oxidant and suggests advantages, viz., simplicity of operation, reduction in time, and an increase in product yields. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Diethyl bromophosphate (DEP); Imidazole; One pot synthesis; Ultrasound

Synthesis, antioxidant, anti-inflammatory, and antimicrobial screening of newer thiophene-fused arylpyrazolyl 1,3,4-oxadiazoles - Mahajan, Pravin S.; Nikam, Mukesh; Chate, Asha; Nimbalkar, Urja; Patil, Vrushali; Bobade, Anil; Chaudhari, Abhay; Deolankar, Dattatray; Javale, Balasaheb; Gill, Charansingh H. (Phosphorus Sulfur and Silicon and the Related Elements, 2015)
A series of newer 1,3,4-oxadiazole derivatives 3a-h, 5a-h containing a thiophene fused with pyrazole moiety of pharmacological significance have been synthesized. The compounds were characterized by H-1 NMR, IR, and mass spectral techniques. The compounds were screened for their in vitro antioxidant, anti-inflammatory and antimicrobial activities. Among them, Compounds 3b (EC50-14.98) and 3f (EC50-12.21) showed significant antioxidant activity. Compound 3a (EC50-15.23) showed good anti-inflammatory activity. Compound 3d was found as the most active derivative against bacterial and fungal strains.
Keywords: 1; 3; 4-Oxadiazole; Anti-inflammatory; Antimicrobial; Antioxidant; EC50; Thiophene-fused pyrazole

Synthesis and antitubercular activity of new benzo[b]thiophenes - Mahajan, Pravin S.; Nikam, Mukesh D.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman; Gill, Charansingh H. (ACS Medicinal Chemistry Letters, 2016)
In vitro and ex vivo efficacies of four series of benzo[b]thiophene-2-carboxylic acid derivatives were studied against Mycobacterium tuberculosis H37Ra (MTB). Benzo[b]thiophenes were also tested in vitro against multidrug resistant Mycobacterium tuberculosis H37Ra (MDR-MTB), and 7b was found to be highly active against A- and DMDR-MTB/MTB (MIC ranges 2.73-22.86 mu g/mL). The activity of all benzo[b]-thiophenes against M. bovis BCG (BCG) was also assessed grown under aerobic and under conditions of oxygen depletion. Compounds 8c and 8g showed significant activity with MICs of 0.60 and 0.61 mu g/mL against dormant BCG. The low cytotoxicity and high selectivity index data against human cancer cell lines, HeLa, Panc-1, and THP-1 indicate the potential importance of the development of benzo[b]thiophene-based 1,3-diketones and flavones as lead candidates to treat mycobacterial infections. Molecular docking studies into the active site of DprE1 (Decaprenylphosphoryl-beta-n-ribose-2'-epimerase) enzyme revealed a similar binding mode to native ligand in the crystal structure thereby helping to understand the ligand protein interactions and establish a structural basis for inhibition of MTB. In summary, its good activity in in vitro and ex vivo model, as well as its activity against multidrug-resistant M. tuberculosis H37Ra in a potentially latent state, makes 7b an attractive drug candidate for the therapy of tuberculosis.
Keywords: Benzo[b]thiophene; Cytotoxicity; M. Bovis BCG; MDR-MTB; Molecular docking

Synthesis, biological evaluation and molecular docking studies of N-acylheteroaryl hydrazone derivatives as antioxidant and anti-inflammatory agents - Mahajan, Pravin S.; Nikam, Mukesh D.; Khedkar, Vijay M.; Jha, Prakash C.; Sarkar, Dhiman; Gill, Charansingh H. (Research on Chemical Intermediates, 2016)
In search of new therapeutics with greater potency, three new series of 3-methyl-1-phenyl-1H-thieno[2,3-c]pyrazole-5-carbohydrazide derivatives have been synthesized and evaluated for their in vitro antioxidant and anti-inflammatory activities. The hydrazones bearing a core pyrazole, chromone and tetrazolo[1,5-a]quinoline scaffold showed promising activities. Interestingly, compounds 3a (EC50 = 06.00 +/- A 2.36) and 5c (EC50 = 07.21 +/- A 0.67) showed the most potent antioxidant activity, while compounds 3a (EC50 = 10.25 +/- A 1.08), 7b (EC50 = 10.50 +/- A 0.99) and 7c (EC50 = 11.18 +/- A 0.15) showed significant anti-inflammatory activity. Furthermore, molecular docking studies also revealed a significant correlation between the binding score and biological activity for these compounds to describe the molecular basis for the structure activity relationship (SAR) results. As these compounds are good cyclooxygenase inhibitors, isoenzyme inhibitory potency studies are warranted.
Keywords: Anti-inflammatory; Antioxidant; Docking study; N-Acylhydrazones; Structure-activity relationship

Organocatalyzed efficient one-pot synthesis, biological evaluation, and molecular docking studies of 4,4-(Arylmethylene)bis-(3-methyl-1-phenyl-1H-pyrazol-5-ols) - Mahajan, Pravin S.; Nikam, Mukesh D.; Khedkar, Vijay; Jha, Prakash; Badadhe, Pravin V.; Gill, Charansingh H. (Journal of Heterocyclic Chemistry, 2017)
The synthesis of 4,4-(arylmethylene)bis-(3-methyl-1-phenyl-1H-pyrazol-5-ol) derivatives catalyzed by ?-proline is a simple, versatile, and efficient method. In vitro antioxidant, anti-inflammatory, and antimicrobial activities of compounds 4a, 4b, 4c, 4d, 4e, 4f, 4g, 4h, 4i, 4j were studied. Furthermore, to rationalize the observed anti-inflammatory activity data, molecular docking study has been performed against COX-2 enzyme which revealed a good binding affinity for these molecules and could provide an insight into the various bonded and non-bonded interactions guiding their binding affinity.